2021
DOI: 10.1101/2021.04.06.438680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-Stimulus Alpha-Band Phase Gates Afferent Visual Cortex Responses

Abstract: The neurogenesis of alpha-band (8-13 Hz) activity has been characterized across many different animal experiments. However, the functional role that alpha oscillations play in perception and behavior has largely been attributed to two contrasting hypotheses, with human evidence in favor of either (or both or neither) remaining sparse. On the one hand, alpha generators have been observed in relay sectors of the visual thalamus and are postulated to phasically inhibit afferent visual input in a feedforward manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…Other studies failed to find such a link (see below) but a recent attention study provided strong evidence in favor of a link between alpha increase and distractor suppression by showing an inverse relationship between alpha power and the Pd component which indexes distractor interference (Zhao et al, 2023; see also Dou et al, 2021;Iemi et al, 2019).…”
Section: Is Alpha Power Increase Related To Proactive Distractor Supp...mentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies failed to find such a link (see below) but a recent attention study provided strong evidence in favor of a link between alpha increase and distractor suppression by showing an inverse relationship between alpha power and the Pd component which indexes distractor interference (Zhao et al, 2023; see also Dou et al, 2021;Iemi et al, 2019).…”
Section: Is Alpha Power Increase Related To Proactive Distractor Supp...mentioning
confidence: 96%
“…A large body of literature shows that the magnitude (and phase) of spontaneous prestimulus alpha oscillations influence visual processing as revealed by stimulus detection measures and event-related potentials (e.g. Iemi et al, 2019;Zazio et al, 2021;Dou et al, 2021;Fakche et al, 2022;VanRullen, 2016). It has therefore been suggested that an alpha power decrease would be associated with an increase sensory excitability, and an alpha power increase would result in a decrease of sensory excitability (see Samaha et al, 2020).…”
Section: Is Alpha Power Increase Related To Proactive Distractor Supp...mentioning
confidence: 99%
See 1 more Smart Citation